2022
DOI: 10.3390/ijerph19148615
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Occurrence of Mental Health Problems in Female Cancer Survivors: A Nationwide Cohort Study

Abstract: The purpose of this study is to determine the effect of cancer survivorship stage and health-related behaviors on the risk of developing mental health problems (depressive and anxiety disorders) in women who have experienced cancers that affect women (breast cancer, cervical cancer, ovarian cancer, endometrial cancer). Using the healthcare utilization and medical checkup data from 2010 to 2020 provided by the National Health Insurance Service, the occurrence of mental health problems since 2020 was tracked for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…Descriptive statistics have displayed that the total sample showed moderate levels of anxiety and adequate scores in PEI dimensions. Our results have confirmed that BC survivors may manifest anxious symptoms even years after treatment 16–20 . However, despite experiencing this adversity, they perceive themselves as effective in attending to, understanding, and repairing their emotions 35 …”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Descriptive statistics have displayed that the total sample showed moderate levels of anxiety and adequate scores in PEI dimensions. Our results have confirmed that BC survivors may manifest anxious symptoms even years after treatment 16–20 . However, despite experiencing this adversity, they perceive themselves as effective in attending to, understanding, and repairing their emotions 35 …”
Section: Discussionsupporting
confidence: 70%
“…Our results have confirmed that BC survivors may manifest anxious symptoms even years after treatment. [16][17][18][19][20] However, despite experiencing this adversity, they perceive themselves as effective in attending to, understanding, and repairing their emotions. 35 In contrast to studies that highlight that BC survivors are more vulnerable to anxiety than the general population, 5 comparisons of means have shown that there were no differences in anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ademais, devido a várias mudanças que o corpo sofre durante o tratamento, também a possível indução da menopausa, alterações hormonais e deformidades nas mamas (KIM et al, 2022;BAQUIÃO;GRINCENKOV, 2019).…”
Section: Introductionunclassified